2011
DOI: 10.1007/s10571-010-9643-4
|View full text |Cite
|
Sign up to set email alerts
|

SNAI1 is Involved in the Proliferation and Migration of Glioblastoma Cells

Abstract: Glioblastoma is the most common type of astrocytoma in the brain. Due to its high invasiveness and chemoresistance, patients with advanced stage of glioblastoma have a poor prognosis. SNAI1, an important regulator of epithelial-mesenchymal transition, has been associated with metastasis in various carcinoma cells. However, its roles in glioblastoma cells have been poorly characterized. To examine roles of SNAI1 in glioblastoma cells, we knockdowned SNAI1 expression using siRNA. SNAI1 siRNA increased the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 33 publications
(41 reference statements)
9
85
0
Order By: Relevance
“…[4][5][6] In GBM, members of the SNAI-family, e.g., ZEB1 and ZEB2, act as EMT activators, enhancing the invasiveness of GBM cells in vitro and in vivo. 7,8 Moreover, EMT processes in GBM cells are also linked to stem-like status, 8 which may cause cellular dedifferentiation of noncancer stem cells, allowing the cells to acquire selfrenewal and tumor-initiating ability. 9,10 Increasing evidence has shown that IR and TMZ inhibit tumor growth in GBM by inducing a type of programmed cell death that is dependent of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] In GBM, members of the SNAI-family, e.g., ZEB1 and ZEB2, act as EMT activators, enhancing the invasiveness of GBM cells in vitro and in vivo. 7,8 Moreover, EMT processes in GBM cells are also linked to stem-like status, 8 which may cause cellular dedifferentiation of noncancer stem cells, allowing the cells to acquire selfrenewal and tumor-initiating ability. 9,10 Increasing evidence has shown that IR and TMZ inhibit tumor growth in GBM by inducing a type of programmed cell death that is dependent of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…40,56 Snail/Slug proteins have already been involved in GBM invasion. 57,58 We demonstrate the regulation of Snail/Slug, in parallel to increased PY142 b-catenin, upon stimulation of GBM cells with HGF. Statistical studies indicate that both nuclear Snail/ Slug and nuclear PY142 b-catenin peak in astrocytomas of grade III.…”
Section: Resultsmentioning
confidence: 79%
“…Some transcriptional repressors such as SNAI-1/2, zinc finger E-box binding homeobox-1 (ZEB-1) and ZEB-2 are able to bind directly to the Ecadherin promoter and repress its transcription. Overexpression of these proteins supports mesenchymal transformation and the change of behavioural characteristics and promotes the continuous acquisition of malignant features by tumor cells [18,19]. Crucial transcription factors involved in EMT are TWIST-1 and signal transducers and activators of transcription-3/-5 (STAT-3/-5).…”
Section: Molecular Principles Of Emtmentioning
confidence: 99%
“…It has been reported that knockdown of SNAI-1 results in decreased invasion and migration of glioma cells. Moreover, SNAI-1 induces expression of matrix metalloprotease-2 (MMP-2), another contributor to EMT progression [18].…”
Section: Molecular Principles Of Emtmentioning
confidence: 99%
See 1 more Smart Citation